2007
DOI: 10.1534/genetics.107.080226
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Spatial Correspondence Between Nonsynonymous Divergence and Neutral Polymorphism Reveals Extensive Adaptation in Drosophila

Abstract: The effect of recurrent selective sweeps is a spatially heterogeneous reduction in neutral polymorphism throughout the genome. The pattern of reduction depends on the selective advantage and recurrence rate of the sweeps. Because many adaptive substitutions responsible for these sweeps also contribute to nonsynonymous divergence, the spatial distribution of nonsynonymous divergence also reflects the distribution of adaptive substitutions. Thus, the spatial correspondence between neutral polymorphism and nonsyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
175
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(191 citation statements)
references
References 52 publications
15
175
1
Order By: Relevance
“…This amounts to only 540/8 = 67 out of 1,054/0.65 = 1,600 expected nonsynonymous substitutions and this may explain why we do not observe reduced synonymous diversity in 10kb windows with more nonsynonymous substitutions (Fig. S6), a pattern previously reported in Drosophila as evidence for recurrent selective sweeps (26). It is possible that many of the X-linked adaptive substitutions in the chimpanzee happened on standing variation as recently reported for humans (27).…”
Section: Resultssupporting
confidence: 69%
“…This amounts to only 540/8 = 67 out of 1,054/0.65 = 1,600 expected nonsynonymous substitutions and this may explain why we do not observe reduced synonymous diversity in 10kb windows with more nonsynonymous substitutions (Fig. S6), a pattern previously reported in Drosophila as evidence for recurrent selective sweeps (26). It is possible that many of the X-linked adaptive substitutions in the chimpanzee happened on standing variation as recently reported for humans (27).…”
Section: Resultssupporting
confidence: 69%
“…Typical populations adapt to changing selection pressures by a surplus of beneficial over deleterious substitutions. Recent population-genetic studies of Drosophila genomes have shown evidence for adaptive evolution at a genome-wide level (37,13,38). Positive fitness flux (with values NΦ of order 10 per genomic substitution) (13) has been inferred from joint estimates of rate and average selection coefficient of point mutations, supporting the conclusion that a substantial fraction of the observed substitutions is adaptive at substantial levels of selection.…”
Section: Applications Of the Theoremmentioning
confidence: 83%
“…Indeed, understanding this underlying distribution of selection coefficients has been a central focus of evolutionary biology over the past five decades (24). Contrary to recent inference made in Drosophila favoring models of frequent recurrent and strongly positive selection (25), but similar to inferences from genome-wide analyses of polymorphisms from S. cerevisiae and S. paradoxus (26), our direct observations in yeast are remarkably consistent with a nearly neutral model of molecular evolution (27), in which a large proportion of new mutations are strongly deleterious and are eliminated via purifying selection, whereas the great majority of remaining mutations are nearly neutral, with dynamics largely dictated by genetic drift (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%